The Concept of Treason in the English Legal System between the Middle Ages and the Reign of the Tudors - Baran, Kazimierz (Díké - Journal of Dezső Márkus Research Group for Comparative Legal History, 2020)
In the Middle Ages the concept of treason in England relied on the 1352 Treason Statute and the interpretation of its clauses. Since statutory list of specimens of treason was considered non-exhaustive, the 1352 law included a proviso that allowed to submit to the king in parliament cases that aroused doubt on whether they were treason or not. This led to the development of Act of Attainder, i. e. semi-judicial procedure which allowed to declare in individual cases some acts to be treasons while applying a typical law-creating modus procedendi (i. e. formulating a bill of Attainder against the alleged perpetrator, the bill had to pass through both houses of parliament and be accepted by the monarch through his assent). The Act of Attainder dynamically developed under the Tudors, particularly during the reign of Henry VIII who used to set it on foot whenever he desired to liquidate his real or alleged opponents. In doing this he could count on parliaments that where docile to him. The henrician Acts of Attainder were characterized by scarcity of evidence furnished to support the accusations, the accused being practically deprived of the possibility to defend themselves. Apart from developing Acts of Attainder, the Tudors took also to modifying the traditional concept of treason and inspired the adoption by parliaments new treason statutes that went beyond the standard at one time set by the 1352 law. The new treason statutes punished utterances considered to be ill-disposed toward the monarch but non-related to any conspiracy. The last decades of the rule of the Tudor dynasty witnessed a slow decline of exploiting the Act of Attainder, however the tendency to resort to the new treason statutes survived.